PEMBERDAYAAN MASYARAKAT PESISIR BERBASIS COMMUNITY BASED MANAGEMENT (Studi Pada Dinas Perikanan Kabupaten Sumenep) - Ida Syafriyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2018)
Coastal area is a rich resource Coastal, marine and fisheries. Coastal areas also have potential that can be developed as a marine tourism area. People who live in the coastal area, since the first also has to depend its life from the utilization of natural resources found in coastal areas.. CBM (Community Based Management) is one approach that will be used in optimizing community empowerment in coastal areas with the CBM approach, not only the economic growth of coastal communities will improve, but also ensure economic growth that can be enjoyed fairly and proportionally. Departement of Fishery Sumenep Regency in coastal community empowerment Community-based refers to the development of entrepreneurs in order to improve the quality of products in production and develop the economy through empowerment that is based on the management of coastal communities industry,